Pemanfaatan Gambir (Uncaria Gambir)Oleh Etnis Pakpak, Kabupaten Pakpak Barat, Provinsi Sumatera Utara - Nova Kristina Bancin; Jamilah Nasution; Abdul Karim (Universitas Medan Area, 2022)
Gambir is one of the products on the gambier plant which has been used by the Pakpak ethnic as traditional medicine from the past until now. This study aims to determine the benefits of gambier and its use by the Pakpak Ethnic community in West Pakpak Regency, North Sumatra. The method used in this study is a qualitative descriptive method through an emic and ethical approach with data collection techniques using semi-structural interview techniques based on a list of questions regarding the benefits of gambier and its use by the Pakpak ethnic community. The results showed that the benefits of gambir is as a treatment, which is categorized as the treatment of minor illnesses and serious illnesses, while the use of gambier is as treatment and care, the use of gambier as a treatment is greater as much as 76% of treatment compared to 24% of treatment. The most widely used way of using gambier is by drinking it. Gambir has the main compound, namely catechins, which are used in treating diseases.